IBNU KHALDUN PENCETUS TEORI SIKLUS - Kandiri Kandiri (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2014)
Social change and social interaction is a particular social circumstances to other social circumstances change, Cycle theory explains there are a number of intermediate stage but its not the end of the the perfect process change, but it will return to the original back experiencing a transition. The factor of social change are 1) social; Families, groups and Ormas, 2) Psychology, 3) Culture. Social change can be seen from the characteristic: 1) development, 2) followed by the other changes, 3) self adaptation, 4) A change is not limited to the material or spiritual aspect.